The Role of Information and Communication Technology in the FP3K Community (Youth Forum Cares for Karo Education) - Ahmad Andrehadi Hasibuan; Niatul Mukarramah; Razkiatul Fitri Matondang; Sherly Alfina; Silvi Hibriyanti; Elfi Yanti Ritonga (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
Humans are basically social creatures. In traditional life, the tendency of humans to live socially can be seen from their daily activities that require interaction with other humans such as fulfilling basic needs. They try to find connectivity with other humans in the search for these needs even though they are in different environments and do not know each other, it is the process that then forms communities which are social groups of several organisms that share an environment that generally has the same interests. The development of technology, especially the Internet, has a great impact on the culture of the community in their activities, the growth of this media has an influence on the culture of the community in interacting and communicating. With various developments of internet media such as social media, blogs, microblogs, web-communities, portals and so on, people can easily interact online or directly at the same time without any geographical, space or time restrictions, they can share anything